2018
DOI: 10.1016/j.conbuildmat.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of earth-based materials: Processing aspects

Abstract: Due to its low environmental impact, earth construction has received much consideration in recent years. Nevertheless, its development remains limited due to low production rate. Recent developments have been made to improve earth-based materials mixdesign and processing methods. Simultaneously, digitally based construction methods have been introduced in the field of construction especially for cement-based materials application. Among these new techniques, the so-called 3D printing by extrusion deposit has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(88 citation statements)
references
References 31 publications
3
84
1
Order By: Relevance
“…The MORs of the UHPFRC matrix and composite in the perpendicular direction are slightly higher than the respective MORs in the lateral direction. This is consistent with the previous studies where the primary load resisting component was either normal strength concrete [17], high performance concrete [10], or geopolymer concrete [7]. The bottom layer carrying the tensile stress during a flexural test was compacted more in the perpendicular direction compared to the lateral direction due to the selfweight of the top layer, which explains the greater MOR in the perpendicular direction compared to that in the lateral direction.…”
Section: Hardened Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…The MORs of the UHPFRC matrix and composite in the perpendicular direction are slightly higher than the respective MORs in the lateral direction. This is consistent with the previous studies where the primary load resisting component was either normal strength concrete [17], high performance concrete [10], or geopolymer concrete [7]. The bottom layer carrying the tensile stress during a flexural test was compacted more in the perpendicular direction compared to the lateral direction due to the selfweight of the top layer, which explains the greater MOR in the perpendicular direction compared to that in the lateral direction.…”
Section: Hardened Propertiessupporting
confidence: 91%
“…At the same time, the material should set quickly to withstand the weight of the subsequent layers deposited above [6]. Few printable concretes with the above combination of properties have been reported in the literature -for example, normal strength concrete [7], geopolymer concrete [8,9], earth-based mortar [10], and high-performance fiber-reinforced cementitious composite (HPFRCC) [11,12]. These materials were designed for a specific printer with particular printing configurations (nozzle type and size, flow rate, pumping specifications, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM) of concrete via 3D printing enables the free-form construction of concrete structures that are irregular in form; much research is ongoing in this area [6][7][8][9][10][11][12]. To secure the structural performance, the methods of evaluating mechanical properties have been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that with the addition of alginate to the earth materials, high productivity was achieved. A sample was prepared and the compressive strength was found to be comparable to traditional construction made with earth materials [80]. Geopolymers have also shown potential in improving sustainability.…”
Section: Sustainable and Eco-friendly Structuresmentioning
confidence: 96%
“…Moreover, the potential of using low impact materials such as raw earth materials and geopolymers adds to the sustainability of the structures. Perrot et al [80] assessed the possibility of printing structures using earth materials. Results showed that with the addition of alginate to the earth materials, high productivity was achieved.…”
Section: Sustainable and Eco-friendly Structuresmentioning
confidence: 99%